2016
DOI: 10.1177/0009922816666854
|View full text |Cite
|
Sign up to set email alerts
|

Nonsuicidal Self-Injury of Adolescents

Abstract: Nonsuicidal self-injury (NSSI) is more common in adolescent and young adult populations than in the past. NSSI is typically used to deal with distressing negative affective states, especially anger and depression, and mixed emotional states. Pediatricians; primary care, family medicine, and emergency room physicians; and mental health professionals are faced with the charge of responding to NSSI behaviors among patients. Physicians in family medicine, pediatrics, and primary care settings play an essential rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Visit-related descriptors included arrival time, whether the child arrived via ambulance, triggers of self-inflicted injury, mechanisms of self-harm, whether the child had suicidal ideation, and disposition classified as either admission to a psychiatric ward, discharge from emergency department, or discharge against medical advice. Triggers for selfinflicted injury were classified into the following categories as described previously 8,9 : interpersonal relationship issues (being angry at someone, wanted to get back at someone); depressive or psychotic symptoms (feeling bored, unhappy, depressed, experiencing delusions or hallucinations); desire to draw attention or express need (wanted to be noticed, wanted others to see my desperation, wanted to avoid having to do something); academic problems (feeling stressed about school, unhappy with performance at school); employment or finance issues (feeling stressed about work, economic hardships); victim of an accusation; or no identified trigger. Multiple mechanisms of injury was defined as more than one intentional injury inflicted within 24 h between each other on arrival at the emergency department.…”
Section: Visit Characteristicsmentioning
confidence: 99%
“…Visit-related descriptors included arrival time, whether the child arrived via ambulance, triggers of self-inflicted injury, mechanisms of self-harm, whether the child had suicidal ideation, and disposition classified as either admission to a psychiatric ward, discharge from emergency department, or discharge against medical advice. Triggers for selfinflicted injury were classified into the following categories as described previously 8,9 : interpersonal relationship issues (being angry at someone, wanted to get back at someone); depressive or psychotic symptoms (feeling bored, unhappy, depressed, experiencing delusions or hallucinations); desire to draw attention or express need (wanted to be noticed, wanted others to see my desperation, wanted to avoid having to do something); academic problems (feeling stressed about school, unhappy with performance at school); employment or finance issues (feeling stressed about work, economic hardships); victim of an accusation; or no identified trigger. Multiple mechanisms of injury was defined as more than one intentional injury inflicted within 24 h between each other on arrival at the emergency department.…”
Section: Visit Characteristicsmentioning
confidence: 99%
“…Clinical studies have discussed multiple associated factors of NSSI include psychological characteristics (such as negative emotionality, deficit in emotion skills, self‐derogation), psychiatric disorders, childhood environmental factors and advertises (Klonsky, 2007). Considering psychological factors, the studies have found that early‐life traumatic events can influence on need to engage self‐injury via managing stress abilities and emotion regulation (Lovell & Clifford, 2016). A systematic review has shown that childhood maltreatment is a significant risk factor for NSSI (Serafini et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Many psychiatric studies from developed countries reported a relationship between attempted suicide and NSSIB. Similarly, numerous psychiatric disorders including depression, anxiety, behavioral disorders, drug abuse, and dissociative, borderline, and antisocial personality disorders are associated with NSSIB and suicidal behavior (4,6,(13)(14)(15)(19)(20)(21)(22)(23)(24)(25). There is no autopsy study in the literature about this relationship.…”
Section: Introductionmentioning
confidence: 99%